2019
DOI: 10.1016/j.tbs.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

How employees view smart cycling to work: A regional survey in the Netherlands

Abstract: The intent of our study is to provide insightful results regarding views and attitudes of employees towards cycling. We were especially interested in their views regarding the use of personalized rewarding schemes delivered via a smartphone app to stimulate cycling to work. The study involved a quantitative on-line survey of employees in Enschede, the Netherlands, and vicinity, wherein 1.800 employees participated. Our results show that most employees commute by bicycle, followed by a considerable percentage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Smartphones were widely used by the population involved in this study. This is in line with recent travel studies carried out in other European countries [60]. However, PNAs installed in smartphones were used by 42% of the respondents in both cities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Smartphones were widely used by the population involved in this study. This is in line with recent travel studies carried out in other European countries [60]. However, PNAs installed in smartphones were used by 42% of the respondents in both cities.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the users of PNAs, Google Maps was the preferred navigation service in both cities, which is in line with recent research [60,63]. The prevalence of Google Maps could be justified by the popularity of the mapping service, the mapping capability across multiple locations globally and by the open-access planning router that can be used for several independent or mixed transport modes [10].…”
Section: Discussionsupporting
confidence: 68%
“…For example, modal shares for the University of Twente sample were comparable to that of a general travel survey among University employees a few years earlier. However, there probably is a self‐selection of employers [33]. Our sample also has a higher fraction of highly educated and high‐income respondents compared to the Dutch Travel Survey 2015 [34].…”
Section: Survey Design and Datamentioning
confidence: 99%
“…The paper by Fioreze et al (2019) provides insight into views and attitudes towards cycling in the Netherlands, often viewed as a "cycling nation". More specifically they studied the extent to which employees who cycle find cycling pleasant, boring, healthy, stressful, refreshing and exhausting, which can all be considered as measures of psychological and physical wellbeing.…”
mentioning
confidence: 99%
“…Like Fioreze et al (2019), most other studies also found a positive relationship between active travel and well-being (Chatman et al, 2019;Handy and Thigpen, 2019;Ye andTitheridge, 2019, de Kruijf et al 2019;Singleton, 2019). For instance, Handy and Thigpen (2019) found that bicycling commuters have the highest commuting satisfaction; Ye and Titheridge (2019) also found this for the high income group; Singleton (2019) found that walking and cycling was related to higher STS, physical and mental health, confidence, positive affect and overall hedonic well-being; Chatman et al (2019) found that an increase in time spent on cycling and an increase in number of visits to friends and relatives on foot, are related to an increase of well-being after moving; and de Kruijf et al (2019) showed that commuters experience an increase in travel satisfaction when switching from car to e-bike.…”
mentioning
confidence: 99%